The latent mediatization of judiciary: A multiple case study on popular trials in Turkey - Özer, Handan Sena Lezgioğlu (İstanbul Bilgi Üniversitesi, 2019)
[Abstract Not Available]
Yargının örtülü medyatizasyonu: Türkiye'deki popüler davalar üzerine bir çoklu vaka analizi